THE USE OF PALM OIL TRUNK POWDER AS FILLERS IN THE MAKING OF GYPSUM CEILING SHEETS WITH POLYURETHANE BINDER - Rahmadhani Banurea; Mulkan Iskandar Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2019)
A study has been conducted on the effect of palm oil trunk powder as fillers in the making of gypsum ceiling sheets for physical, mechanical, and DTA properties. The type of adhesive used is a polyurethane binder. Palm oil trunk powder is varied in 5, 10, 15, 20, and 25 g. The results showed that the physical properties (density of 1.6 g/cm3 and water absorbency of 15.08%) in the composition of 5 grams of palm oil trunk powder were the best results. The higher the powder level the higher the density value but the lower the water absorbency. The results of the physical properties test still meet the standards of SNI 03-2105 1996 and are still above the physical properties of the Jaya Board gypsum ceiling. The results of mechanical test (impact test 2.0 x 10-4 J/mm2, tensile test 305.8 kPa, flexural strength test/MOE 7233.8 kg/cm2, and fracture strength test/MOR 13.44 MPa) were the best results and at composition of 25:25:15. This composition is the most homogeneous composition so that its mechanical properties are optimum. Keywords: ceiling sheets, palm oil trunk powder, and polyurethane.